Cystic Fibrosis Transmembrane Conductance Regulator Modulators: The End of the Beginning - Barry, Peter J.; Ronan, Nicola; Plant, Barry J. (Seminars in Respiratory and Critical Care Medicine, 2015)
Cystic fibrosis (CF) represents one of the success stories of modern medicine with sustained incremental increases in the survival from one of childhood death to one of adult survival into the middle decades over the past 30 years. Improving survival has focused on multidisciplinary management centered on treating the consequences of this genetic disease. It has been firmly established for more than 20 years that mutations in the CF transmembrane conductance regulator (CFTR) gene result in a defective protein that normally functions as a chloride channel on epithelial cell surfaces. Until recently, modulating CFTR dysfunction was only a research aspiration, however, greater focus placed upon addressing the primary defect of CF has developed several clinical therapeutic strategies in this area. This review highlights the evidence to date on efforts to modulate CFTR and restore robust functional protein to the cell surface. This approach has now led to the licensing of one CFTR potentiator, which has been shown to have significant clinical improvements in a subset of CF patients. This success represents the beginning for CFTR modulation and further research is ongoing which aims to broaden the applicability of these techniques.
Keywords: cystic fibrosis; modulation; therapy; CFTR; genetics; potentiator; corrector